Leadership of Christian Religious Education Teachers in Classroom Management - Heldy Jerry Rogahang (Institut Agama Kristen Negeri Manado, 2022)
The aim of this research is to find the type of leadership of Christian Religious Education teachers in classroom management at SMP Negeri 8 Manado. The type of research used in this research is qualitative research. Determining the data source used a purposive sampling technique, consisting of school principals, teachers and students. Data collection techniques use observation, interviews and documentation methods with the research instruments being the researchers themselves. The data analysis technique uses Miles and Huberman data analysis techniques, namely data reduction, data display, and verification. The results of the research show that the leadership type of Christian religious education teachers at SMP Negeri 8 Manado in managing the class does not dominate one type of leadership. Sometimes teachers apply an authoritarian type of leadership, but classroom management that takes place during the learning process requires initiative from the teacher to become a democratic teacher of his students.